HETEROGLOSSIC ENGAGEMENT PATTERNS IN THE TIKTOK, INC. VERSUS GARLAND ORAL ARGUMENT TRANSCRIPT - Rio Nur Rachmad; Ni Gusti Ayu Roselani (MABASAN, 2025)
The present study examines how U.S. Supreme Court participants, including judges and lawyers, manage these viewpoints in the TikTok, Inc. versus Garland oral argument transcript by using an engagement system that focuses on the heteroglossic subtype, where speakers acknowledge other perspectives to support or challenge them. The study employs a discourse analysis approach. The data were sourced from the oral argument transcript on the U.S Supreme Court official website. The study applies the The UAM Corpus Tool, a software developed at the Universidad Autónoma de Madrid, was used to manually annotate engagement markers in the dataset and categorise words, phrases, clauses, and sentences, examining heteroglossic engagement by analysing how speakers opened up space for other views or closed it down in arguments. The study found that both judges and lawyers frequently used strategies to limit opposing views. Judges often denied claims directly and weighed opposing arguments to demonstrate that they were unreasonable. While lawyers conceded minor points only to return to their main arguments, the expansions were also identified, which allowed the judges to entertain possibilities by using specific phrases to discuss ideas openly. Conversely, lawyers acknowledged the other side’s points before arguing against them.